Respon Hasil Jagung Manis Terhadap Takaran Pupuk Fosfat pada Andisol Lembang - Endang Sufiadi (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2011)
An experiment was conducted at experimental field of BBHAT, Cikole Lembang, West Java District, West Java, on elevation of 1.250 m above sea level, from July to October 2008. The objective of this experiment was to study the Yield Response of Sweet Corn on the Phosphate Fertilizer Rates in Lembang Andisol. The design used was a Randomized Block Design with five treatments and five replication of A = without phosphate fertilizer, B=75 kg ha-1 P2O5, C= 150 kg ha-1 P2O5, D=225 kgha-1 P=O5, E=300 kg ha-1 P2O5. The result of experiment showed that yield response of sweet corn on the phosphate rate in Lembang Andisol is quadratic form. Maximum yield of corn cob with husk per plant of 575,24 grams per plant was obtained at the optimum phosphate rate of 190,7 kg ha-1 P2O5. This corn yield is equivalent to 22 tons ha-1 higher than the potential yield of these sweet corn variety. Soil-available P increased with increasing rates of phosphate fertilizer, reaches a very high criteria.